Respon Masyarakat Adat Bolivia terhadap Kebijakan War on Drugs Amerika Serikat di Bolivia - Subamia Uttari, Sagung Uttami; Fasisaka, Idin; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
This research aimed to explain the impact of the United States War on Drugs policy that led the social movements of indigenous peoples in Bolivia through the appearance of Evo Morales and formation of El Movimiento al Socialismo or Movement towards Socialism (MAS) which become an influential political party in Bolivia and eventually led Evo Morales to become the first indigenous President of Bolivia in 2006 and point the concern of indigenous peoples through 2009 Constitution and ratification of the 1961 Convention. Data was obtained through library methods such as, scientific journals, related websites, books, ande-books. Collected datadescribed through qualitative research method with descriptive research type. Research analysis used the concepts of rights of indigenous peoples and self-determination. Both of these concepts explain how United States intervention through War on Drugs that becomingthe trigger of Bolivian indigenous people’s self-determination effort. Keywords:War on Drugs, Coca Leaves, Rights of Indigenous Peoples, Self-Determination